Dietary Exposure and Health Risk Assessment of Aflatoxin M1 in Dairy Products Consumed by Population in North Macedonia - Gordana Ilievska; Biljana Stojanovska-Dimzoska; Dushica Koceva; Goran Stojkovic; Aleksandra Angeleska; Elizabeta Dimitrieska-Stojkovikj (Shahd Sadoughi University of Medical Sciences@ Health Services, 2022)
Background: Aflatoxins (AFs), as secondary metabolites, are mainly produced by fungi of Aspergillus genus. The determination of contamination rate, dietary exposure, and health risk assessment for aflatoxin M1 (AFM1) was conducted aimed to estimate potential health risks for the population of North Macedonia. Methods: A total of 974 dairy samples, including 404 Ultra-High Temperature (UHT) milk, 291 ice cream, 178 yogurt, and 101 cheese were collected from the markets in North Macedonia. Analysis of AFM1 was done using Enzyme-Linked Immunosorbent Assay and High-Performance Liquid Chromatography with Fluorescence Detection Results: The AFM1 incidence was highest in yogurt samples (93.8%) and lowest in UHT milk samples (67.8%). AFM1 concentrations were 49.1±68.4, 30.9±30.0, 35.1±40.4, and 40.1±90.1 ng/kg for UHT milk, ice cream, yogurt, and cheese samples, respectively. The Estimated Daily Intake (EDI) for the average population and high consumers (upper bound; samples with AFM1
Keywords: Aflatoxin M1, Milk, Dairy Products, Risk Assessment, Republic of North Macedonia